Role and Performance(s) of MSMEs in Indian Economy - Dr. H M Naveen, (International Journal of Scientific Research in Science and Technology, 2024)
The MSME sector has emerged as a highly vibrtant and dynamic sector in the Indian economy. It contributes significantly in the economic and social development of the country. MSMEs are complementary to large industries as supportive units and it contributes significantly in the inclusive development of the country. The MSMEs are widening their domain across sectors of the economy, producing diverse range of products and services to meet the demands of domestic as well as global market. An overview and performance of MSME Sector in the country is provided in this article in terms of role of MSMEs in Indian economy ; key results of NSS survey on MSMEs. A Comparative analysis of MSMEs in the top of 10 states ; and the Registration of new MSMEs.
Keywords: Role; Performance; MSME; Indian Economy